Five-Year-Old Preschoolers’ Sharing is Influenced by Anticipated Reciprocation - Xiong, Mingrui; Shi, Jiannong; Wu, Zhen; Zhang, Zhen (Frontiers in Psychology, 2016)
Whether children share in anticipation of future benefits returned by a partner is an interesting question. In this study, 5-year-old children and an adult partner played a sharing game, in which children donated first and the partner donated afterward. In Experiment 1, the partner’s resources were more attractive than the child’s. In the reciprocal condition, the child was told that s/he would be a recipient when the partner played as a donor. In the nonreciprocal condition, however, the child was told that an anonymous child would be the recipient when the partner donated. Results showed that children shared more with the partner when they knew that they would be a recipient later. In Experiment 2, the child was always the recipient when the partner donated, but the partner’s resources were more desirable than the child’s in the high-value condition, and less desirable in the low-value condition. We found that children were more generous when the partner’s resources were valued higher. These findings demonstrate that 5-year-old preschoolers’ sharing choices take into account the anticipated reciprocity of the recipient, suggesting either self-interested tactical sharing or direct reciprocity in advance of receiving. Specifically, they adjust their sharing behavior depending on whether a partner has the potential to reciprocate, and whether it is worth sharing relative to the value of the payback.